CARACTERIZAÇÃO PETROGRÁFICA E GEOQUÍMICA DE DIQUES MESOZÓICOS À NORDESTE DE RIO BRANCO DO SUL, PR - G. A. Vanzela, G. A.; Vasconcellos, E. M. G.; de Mesquita, M. J. M.; Pinese, J. P. P. (Geochimica Brasiliensis, 2012)